Belas for the Prevention of Child Marriage among Sasak Community, West Lombok - Kartikawati, Reni; Sri Natih, Ni Nyoman; Ratri, Sari Damar (Masyarakat: Jurnal Sosiologi, 2023)
This paper aims to evaluate the compatibility of the belas mechanism, which separates prospective brides still considered children (merariq kodeq), in West Lombok Regency with the provisions of Child Protection Law No. 35/2014. While prior research in various countries has primarily focused on interventions and child marriage prevention programs, this study takes a different approach by examining the intricate relationship between children (those under 18 years of age) and the broader social system. To comprehensively explore this relationship, our team adopts Bronfenbrenner's socio-ecological model, which encompasses various stages of a child's life. This model considers individual biology, interactions with diverse actors, environmental factors, and cultural and structural influences. Our study's findings reveal that the current implementation of the belas mechanism does not adequately align with the principles of child protection. This inadequacy is particularly evident in terms of the psychological well-being and vulnerability of girls who become victims of child marriage, especially in unique situations involving girls who experience unwanted pregnancies. To conduct our research, we employed qualitative methodologies, including participant observation and in-depth interviews. These methods allowed us to engage with primary subjects, five girls aged 14–18 years, as well as key stakeholders such as representatives from children's forums, village child protection commissions, religious leaders, parents, teachers, and others.